Impact of Nutritional Milk for Lactating Mothers upon Efficiency of Breast Feeding for Iraqi Mothers at Maternity Hospital in Baghdad City - Hawraa Hussein Ghafel1, Bahaulddin Hassan Abbood2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective: This study conducted to find out: The impact of nutritional milk for lactating mothers upon efficiency of breast feeding 2.The impact of nutritional milk for lactating mothers upon the number of breastfeeding 3.The impact of nutritional milk for lactating mothers upon t babies’ weight. This study conducted at AL-Elwaya Maternity Hospital in Baghdad City. The study started in January 2019 to march 2019. The study sample included (100) lactating mothers that feed their newborns by breast feeding only despite of the method of delivery (normal vaginal delivery & caesarian section) this sample divided in two groups the first one is the( study group) consist of (50) lactating mothers that consumption nutritional milk for three weeks and the other (control group ) consist of (50) lactating mothers that not consumption nutritional milk and then comparison between the two groups to detecting the impact of nutritional milk on the efficiency of breast feeding . results showed that the nutritional milk have impact upon the efficiency of breast feeding for the lactating mothers who were consumption the nutritional milk for at least three weeks and have impact upon their babies’ weight and growth.